G278(P) Development of successful and sustainable paediatric oncology shared-care networks in low-middle income countries. (12th March 2018) - Freccero, P; Burns, E; Collington, M; Khaing, A; Renner, L; Paintsil, V; Islam, A; Dolendo, M; Eden, T
Abstract : Background/Aims: World Child Cancer has created twinning partnerships with developing oncology services in low-middle income countries (LMICs) to support improvement of services for children with cancer. Central to success for these is the creation of effective shared-care networks not just single centre support.There is a dearth of good literature on network development. Our aim was to create an ideal model. Methods: The model was developed through learning from a 3 year UK Government(DFID) funded programme in Ghana and Bangladesh in which new shared care units were created and from lessons shared from other WCC-funded programmes in Myanmar and the Philippines. A 2 dayworkshop was held, focussing on lessons learnt from paediatricians representing networks in different stages of development to identify key elements and steps necessary to optimise planning. Results: The over-arching proposed themes for the model were need for; excellent, regular communication between the centres;twinning partnerships and funding.A succesful shared- care network must have a strong hub hospital at its centre with at least one fully trained paediatric oncologist and a committed multi-disciplinary team. The hub (referral) centre must have dedicated space/beds, develop treatment guidelines and protocols and provide training for the staff populating the satellite units.Shared- care centres must, be strategically chosen based on population demography and accessibility, create development plans and service provision to replicate the hub centre as close as resources allow… Collaborative working and good communication, using the same treatment protocols, developing two-way referral systems and sharing successes and any failures are essential. Sustainable development is ensured through a step -by step process, funding support, and ongoing opportunities within the network. Conclusion: We hope that this model can be shared to enable others to access it and help iinform their systems development. Whilst the model is not exhaustive and requires further research, it represents a first step, with lessons learnt from paediatricians with actual experience of creating such networks. Hub and spoke service provision better meets the needs of all children no matter where they live in the world.